ANALYSIS OF ACCOUNTABILITY AND TRANSPARENCY IN THE MANAGEMENT OF POLITICAL PARTY ASSISTANCE FUNDS AT THE NATIONAL UNITY AND POLITICS AGENCY (KESBANGPOL) OF SOUTH LAMPUNG REGENCY - Dodi Hernaldi; Agus Purnomo (International Journal of Multidisciplinary Reseach, 2026)
The research method used is descriptive qualitative research. This method is used to describe the analysis of accountability and transparency in the management of political party funds at the National Unity and Politics Agency in South Lampung Regency. All data were obtained directly from informants in the field using interviews and document studies. The results of the study indicate that, in general, the management of political party funds at National Unity and Politics in South Lampung Regency has been implemented in accordance with statutory provisions. However, the level of accountability and transparency is not yet optimal. This is evident in the limitations in financial and administrative accountability, as well as the lack of transparency in information and procedures. The accountability mechanism is in place, but still needs strengthening to be more effective, consistent, and transparent Inhibiting.